Analisis Pengaruh Sharing Ekonomi Terhadap Pertumbuhan Ekonomi Indonesia - Afiful Hadi Yustino; Marta, Joan (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study was conducted to determine the effect of technology adoption on economic growth in Indonesia, the effect of the labor force participation rate on economic growth in Indonesia, and the effect of peer to peer lending on economic growth in Indonesia. This study uses secondary data sourced from the Central Statistics Agency of Indonesia and the Financial Services Authority. This study is descriptive and inductive, the data used is secondary data from 34 provinces in Indonesia in 2020-2023. This study uses panel data regression with the Fix Effect Model (FEM) approach assisted by eviews 12 software. The results of this study indicate that (1) the value of technology adoption has a positive and significant effect on economic growth in Indonesia (2) the labor force participation rate has a significant positive effect on economic growth in Indonesia. (3) peer to peer lending has a negative and significant effect on economic growth in Indonesia.